The Translating of Screenplays in the Mainland of China - Zhang, Chunbai (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThis essay discusses the translating of screenplays for dubbing in the mainland of China. It is shown that, besides the basic requirements of immediate comprehensibility and lip synchronization, the dubbing of foreign films and TV series into Chinese is subject to a number of linguistic, cultural and political constraints, which in turn put a limit on the “exotic” space in the dubbed films and TV series. A number of relevant translation strategies are then discussed, including literal translation, reduction of the original image to sense, and deletion. It is emphasized that since the basic principle of screen translation should be one of equivalent effect, the translator should endeavor to reduce the processing effort of the audience. Furthermore, it is pointed out that this “exotic” space has been increasing along with the narrowing of the cultural gap between China and the West.